Factors of Muslim Fashion Progress in Surakarta City: A History Review - Laela Puji Utami (Islah: Journal of Islamic Literature and History, 2021)
Nowadays, Muslim fashion is worn not only to fulfil Islamic sharia, but also to present Muslim fashion without ignoring the beauty of the fashion itself. Therefore, in its progress, Muslim fashion comes with varied, trendy and fashionable items. Examining Muslim fashion progress in Surakarta City, the researcher tries to find out the background of Muslim fashion widely known of Muslim in Surakarta City and factors causing the rapid progress of Muslim fashion in Surakarta City. This study uses historical method by using procedures in accordance with the rules and the regulations of historical writing. The findings shows that Muslim fashion in Surakarta City is influenced by some factors including: (1) the occurrence of Islamization during The New Order era in Surakarta City; (2) the entry of Ikhwanul Muslimin Thought and the occurrence of Iranian Revolution; (3) the variation of Islamic colours in Surakarta city including traditionalist, puritans, modernist, and radical; (4) the high number of middle class Muslims with a consumptive lifestyle; (5) the history of Surakarta City as the birthplace of Serikat Dagang Islam (SDI) and batik textile producer in Indonesia; (6) the existence of shopping centres, fashion houses, boutiques, and Muslim fashion shops; (7) the existence of Solo Hijabs Community in introducing and promoting Muslim fashion; and (8) the role of Ikatan Perancang Busana Surakarta (IKAPERSTA), a fashion designers association in Surakarta city, representing activities related to fashion in Surakarta City